Helicobacter pylori activates the early growth response 1 protein in gastric epithelial cells - KELLEHER, DERMOT P (American Society for Microbiology, 2004)
The early growth response 1 (Egr-1) transcription factor is rapidly induced by various stimuli and is implicated in the regulation of cell growth, differentiation, and gene expression. The aim of this study was to examine the effect of Helicobacter pylori on the expression of Egr-1 and Egr-1-regulated genes in gastric epithelial AGS cells. Egr-1 expression was assayed by immunoblotting and electrophoretic mobility shift assays using H. pylori-stimulated AGS cells. Transient transfection experiments with promoter-reporter constructs of CD44, ICAM-1, and CD95L were used for expression studies. H. pylori induced the expression of Egr-1 in gastric epithelial cell lines in a dose-dependent manner, with the rapid kinetics that are typical of this class of transcription factors. Immunohistochemical studies of biopsies revealed that Egr-1 expression is more abundant in H. pylori-positive patients than in uninfected individuals. Reporter-promoter transfection studies indicated that Egr-1 binding is required for the H. pylori-induced transcriptional promoter activity of the CD44, ICAM-1, and CD95L (APO-1/Fas) constructs. The blocking of egr-1 with an antisense sequence prevented H. pylori-induced Egr-1 and CD44 protein expression. The MEK1/2 signaling cascade participates in H. pylori-mediated Egr-1 expression, but the p38 pathway does not. The data indicate that H. pylori induces Egr-1 expression in AGS cells in vitro and that the Egr-1 protein is readily detectable in biopsies from H. pylori-positive subjects. These observations suggest that H. pylori-associated Egr-1 expression may play a role, in part, in H. pylori-induced pathology.
PUBLISHED
Keywords: Clinical Medicine